Rapid differentiation of new isolates with MALDI-TOF mass spectrometry via discriminant function analysis based on principal components - (:unkn) unknown (KOREAN INSTITUTE CHEMICAL ENGINEERS, 2009)
Discriminant function analysis based on principal components was applied to the spectral outputs of whole cell suspensions of nine isolates from matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry. First, based on the salt tolerance and whole cell proteins, the similarity of the isolates to moderate halophiles was established. Intact microorganisms were then inferentially clustered by MALDI-TOF mass spectroscopy taking four type strains as precursors. Two of these type strains were moderate halophilic bacteria (Halomonas salina and Halomonas halophila), one was a mesophilic bacteria (Escherichia coli), and one was a halophilic archaea (Haloarcula vallismortis). Results showed that the isolates were significantly similar to halophiles but were different from a mesophile. This investigation demonstrates the feasibility of using whole cell suspensions for rapid differentiation prior to extensive experimentation.
Keywords: Hierarchical Clustering; Discriminant Function Analysis; Principal Component Analysis; Intact Microorganisms; MALDI-TOF-MS; DESORPTION IONIZATION-TIME; PROTEINS; BACTERIA; STRAINS; IDENTIFICATION; MICROORGANISMS; BIOLOGY; CELLS; COLI